2004
DOI: 10.7547/0940558
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5-Degree Valgus and Varus Rearfoot Wedging on Peak Hallux Dorsiflexion During Gait

Abstract: The dynamic effects of 5° varus and valgus rearfoot wedging on peak hallux dorsiflexion were investigated in 30 asymptomatic subjects (5 males and 25 females). Statistically significant reductions in peak hallux dorsiflexion were found with rearfoot varus wedging and rearfoot valgus wedging. Furthermore, the reduction in peak hallux dorsiflexion occurring with rearfoot varus wedging was statistically significant compared with that associated with rearfoot valgus wedging. These findings have implications for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…While two studies have reported increases in first MTPJ dorsiflexion with orthoses placed under the foot in static stance [85,86], one study reported no change in first MTPJ dorsiflexion [87]. Gait studies have been similarly inconsistent, with two studies reporting a decrease in first MTPJ dorsiflexion (with medial wedging [88] and orthoses [34]) and one study reporting no change [35]. …”
Section: Discussionmentioning
confidence: 99%
“…While two studies have reported increases in first MTPJ dorsiflexion with orthoses placed under the foot in static stance [85,86], one study reported no change in first MTPJ dorsiflexion [87]. Gait studies have been similarly inconsistent, with two studies reporting a decrease in first MTPJ dorsiflexion (with medial wedging [88] and orthoses [34]) and one study reporting no change [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Smith y cols. (9) confi rman, en otro estudio que cuñas de 5º de valgo a nivel del retropié aumentan la fl exión dorsal de la primera articulación metarsofalágica en dinámica, como en el estudio de Munuera y cols. (7) donde utilizan ortesis para disminuir la pronación, demostrando que hay una relación entre el aumento pronación del pie y el hallux limitus.…”
Section: Relación Del Hallux Limitus Con El Aumento De La Pronaciónunclassified
“…Pero en cambio, en estática no hay muchos artículos, de ahí la importancia de estos tipos (9) (*) Articulación metatarsofalángica 6. BIBLIOGRAFIA de estudio, como el estudio de Paton (15) que demuestra que, existe una relación entre la disminución de la fl exión dorsal del hallux en estatica, Hallux Limitus Estructural y la pronación a nivel de la articulación mediotarsiana con la prueba del Navicular Drop en estática.…”
Section: Relación Del Hallux Limitus Con El Aumento De La Pronaciónunclassified
See 1 more Smart Citation
“…Several authors 9,10 have previously shown that a change in the position of the foot using varus or valgus wedges can increase hallux dorsiflexion. One study 11 investigated the effect of modified Root orthoses on maximum hallux dorsiflexion.…”
Section: Review Of the Literaturementioning
confidence: 99%